Adaptability Analysis of Full Height Mining at One Time of Deep Soft Thick Coal Seam - Li, Qinghai; Wang, Haonan; Zheng, Xuejun; Li, Kaixin; Ji, Yonghu; Wang, Zijun (Frontiers in Earth Science, 2022)
With the improvement of technology and equipment, it is preferred to adopt full-height mining at one time when conditions permit. According to the specific geological conditions of no. 3 coal seam in Lilou Coal Industry, the feasibility of full-height mining and top-caving mining method for soft thick coal seam with large buried depth is analyzed by means of theoretical analysis, numerical simulation and field application analysis, which provides basis for the subsequent improvement of field mining method. Through the establishment of cantilever beam mechanical model of basic roof, the influence of two mining methods on the energy response of basic roof is analyzed. Based on the energy storage characteristics of coal seam, roof and floor measured in the field, the intensity of energy released from disturbed strata by two coal mining methods is analyzed. PFC2D numerical simulation was used to compare the roof failure of the two mining methods, to monitor the change of the stress in the coal seam after excavation, and to calculate the coal seam burial depth suitable for a full mining height by adjusting the in-situ stress. The results show that compared with top-coal mining, the elastic strain energy accumulated in the full-height roof beam is more, and the energy release intensity of disturbed rock is greater. The roof crack extension height is 9.1 m and the coal wall failure depth is 5.46 m under the condition of full mining height at one time. The roof crack extension height is 1.19 m and the coal wall failure depth is 2.19 m under the caving coal mining method. In the caving coal mining method, the stress level of the original rock is restored at 3 m in front of the coal wall, and the stress level of the original rock is restored at 5 m in front of the coal wall when the full mining height is once taken. It is safer to adopt full-height mining method when the buried depth of coal seam is less than 380 m. The research results can provide reference for mining soft thick coal seam with large buried depth.